2011
DOI: 10.1007/s10529-011-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Indigo biosynthesis by Comamonas sp. MQ

Abstract: An indigo-producing strain was isolated from activated sludge and identified as Comamonas sp. based on 16S rRNA analysis. It produced indigo at 26.5 mg/l with a conversion of indole to indigo of 47%. Indole at 50 mg/l plus 200 mg naphthalene/l gave 32.2 mg indigo/l with a 58% conversion. A pathway for indigo formation is proposed. This is the first study of indigo biosynthesis by Comamonas sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 12 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, the indigo formation by Pseudomonas sp. HAV-1 was superior when compared to other reported studies for indigo production ( Table 2 ) [ 21 , 22 ]. This implies that Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, the indigo formation by Pseudomonas sp. HAV-1 was superior when compared to other reported studies for indigo production ( Table 2 ) [ 21 , 22 ]. This implies that Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 67%
“…Besides, product V with a retention time of 10.1 min and a prominent molecular ion (M-H) − peak at m/z 146.0246 (C 8 H 5 NO 2 ) was identified as isatin by comparing its mass spectral data with standard chemical and previous studies (Fig. 2e) [26,27]. Product VI was detected at retention time of 12.7 min with a prominent molecular ion (M-H) − peak at m/z 132.0454 (C 8 H 7 NO) (Fig.…”
Section: Mechanisms Of Indigoids Production By the Two Phenol-degradimentioning
confidence: 83%
“…In addition, indoxyl could be further hydroxylated to produce isatin [14,28]. Besides, isatin could also be obtained through the decomposition of indigo [26,28]. Previous studies indicated that the C-3 oxidation pathway of indole biotransformation usually occurred in accompany with C-2 and C-7 oxidation pathways, leading to the formation of 2-hydroxyindole (2-oxindole) and 7-hydroxyindole, respectively [14,29,30].…”
Section: Mechanisms Of Indigoids Production By the Two Phenol-degradimentioning
confidence: 99%
See 1 more Smart Citation
“…While the productivity (135 mg/L) was still modest, this demonstrated that a fermentative approach can be effective. Since then, many other aromatic hydrocarbon-degrading bacteria have been identified and studied for their capability to produce indigo, often with indole as precursor (O'Connor and Hartmans 1998;Bhushan et al 2000;Alemayehu et al 2004;Pathak and Madamwar 2010;Qu et al 2012b). While many of these bacteria are pseudomonads, other bacteria have also been found to harbor NDOs that can be used to produce indigo (Mercadal et al 2010;Qu et al 2010).…”
Section: Naphthalene Dioxygenasesmentioning
confidence: 99%